Marketing Strategy Using Porter's Five Force Model Approach: A Case Study of PT M-150 Indonesia - Apriyanti, Eka (HM Publisher, 2021)
The right strategy is an absolute necessity for a company. This study aims to formulate the right marketing strategy with the Porter's Five Force approach, namely rivalry among competing firms, Bargaining power of customers, Bargaining power of suppliers, Potential development of substitutes or substitution products, and potential entry of new competitors. The research uses qualitative methods based on interviews to gather information. Interviews were conducted with the general manager, national sales manager, logistic manager, and marketing manager to ensure that the information complete. Results show that currently, PT M-150 Indonesia has a weak positioning compared to competitors' products. PT M-150 Indonesia has not been able to distribute its products to all layers of the market and M-150 products get a negative perception in society that these products will harm health. With these results, it is concluded that the right strategy to use is a strategy to create new value so that product positioning is stronger, strengthen distribution channels so that products are available in the market, besides that, socialization must be carried out by PT M-150 Indonesia to eliminate negative perceptions of the product.